A Comparison of Two Alternate Scaling Approaches Employed for Task Analyses in Credentialing Examination Development. Issue 1 (22nd May 2018) - Fidler, James R.; Risk, Nicole M.
Abstract: Credentialing examination developers rely on task (job) analyses for establishing inventories of task and knowledge areas in which competency is required for safe and successful practice in target occupations. There are many ways in which task‐related information may be gathered from practitioner ratings, each with its own advantage and limitation. Two of the myriad alternative task analysis rating approaches are compared in situ : one establishing relative task saliency through a single scale of rated importance and another employing a composite of several independent scales. Outcomes regarding tasks ranked by two practitioner groups are compared. A relatively high degree of association is observed between tasks ranked through each approach, yielding comparable, though not identical examination blueprints.